Diverse in vitro and in vivo anti-inflammatory effects of trichlorido-gold(III) complexes with N6-benzyladenine derivatives - Křikavová, Radka; Hošek, Jan; Suchý, Pavel; Vančo, Ján; Trávníček, Zdeněk (Journal of inorganic biochemistry, 2014)
A series of gold(III) complexes involving differently substituted derivatives of a plant hormone N6-benzyladenine (HL1-5) is reported. The complexes have the general formula [Au(HL1-5)Cl3]∙nH2O (n=0 for 1, 3-5; and n=1 for 2), where N6-(2-fluorobenzyl)adenine (HL1), N6-(2-chlorobenzyl)adenine (HL2), N6-(3-chlorobenzyl)adenine (HL3), N6-(4-chlorobenzyl)adenine (HL4) and N6-(4-methylbenzyl)adenine (HL5) represent the N9-coordinated ligands. The results of thorough characterization (elemental and thermal analyses, FT-IR, Raman and NMR spectroscopies, ESI+ mass spectrometry, conductivity measurements, DFT calculations) showed that the presented complexes 1-5 involve a central gold(III) atom coordinated in a square-planar geometry by the N9 atom of the purine moiety of HL1-5 and by three chlorido ligands. The complexes (1-5) were studied in vitro for cytotoxicity and anti-inflammatory activity on LPS-activated macrophages (THP-1 cell line), and in vivo for anti-inflammatory effects (1, 2, 5) using the carrageenan-induced hind paw oedema model on rats. Surprisingly, the results on the in vitro level revealed that the complexes show negligible cytotoxicity and anti-inflammatory activity, however, the activity on the in vivo level was found to be significant, fully comparable with the utilized drug Indomethacin, or even better as compared to a gold-containing metallodrug Auranofin.
Keywords: zadní končetina; kinetin; Hindlimb; auranofin; Indomethacin; Male; Chlorides; nádorové buněčné linie; Rats; Cell Line, Tumor; lidé; Humans; potkani Wistar; Edema; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; monocyty; Animals; viabilita buněk; Monocytes; zvířata; Gold; ligandy; mužské pohlaví; chloridy; Coordination Complexes; zlato; krysa rodu Rattus; Kinetin; Auranofin; Rats, Wistar; komplexní sloučeniny; edém; Cell Survival; Ligands; indomethacin